Negotiating boundaries: (A qualitative study of) mental health professionals’ demarcation of psychiatric diagnosis in everyday practice - Jonathan Munch Bach; Klaus Nielsen; Henriette Bruun (SSM - Mental Health, 2025)
The purpose of this article is to explore how mental health professionals make use of and negotiate the boundaries of psychiatric diagnosis in their everyday practice. The study is based on empirical material from four months of participant observation and interviews conducted in both inpatient and outpatient psychiatric clinics in Denmark.In this article, we demonstrate how diagnoses are not only used to describe the condition of a patient, but also to decide questions of agency, to render certain problems practicable, and to demarcate the boundaries of their practice.Finally, we show how these negotiations hold consequences for the trajectories of care offered to patients and propose the notions of situated rationality and psychiatry as a multiple institution as important terms to understand the everyday practice and negotiations of mental health professionals.